The Effect of Service Quality on Customer Satisfaction (Case Study of Pt. Pegadaian Persero Paniki Branch Service Unit) - Rundengan, Margaretha Annatje; Manopo, Meiske; Ponggohong, Edryl Henok Prasetya (Asian Journal of Logistics Management, 2024)
Service and customer satisfaction are two variables that are closely related. This is the case with employee services to customers / customers of PT Pegadaian UPC Paniki, where several service indicators such as, affect customer satisfaction. This study aims to determine the effect of service quality as measured by physical evidence, reliability, responsiveness, assurance, and empathy, on customer satisfaction at PT Pegadaian (Persero) Paniki Branch Service Unit. This type of research is qualitative and uses primary and secondary data. Secondary data is obtained from various sources such as journals and books, while primary data is obtained by distributing questionnaires to respondents. The sampling technique used simple random sampling method, obtained a sample size of 45 respondents. By using Service Quality Analysis. The results showed that physical evidence, reliability, responsiveness, assurance and empathy had a positive effect on existing customer satisfaction. This shows that PT Pegadaian (Persero) Paniki Branch Service Unit must provide better service, especially those related to customer speed and complaints arising from customers.